2013
DOI: 10.3389/fncel.2013.00091
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CRH receptor type 1 expressed on glutamatergic neurons increases excitability of CA1 pyramidal neurons by the modulation of voltage-gated ion channels

Abstract: Corticotropin-releasing hormone (CRH) plays an important role in a substantial number of patients with stress-related mental disorders, such as anxiety disorders and depression. CRH has been shown to increase neuronal excitability in the hippocampus, but the underlying mechanisms are poorly understood. The effects of CRH on neuronal excitability were investigated in acute hippocampal brain slices. Population spikes (PS) and field excitatory postsynaptic potentials (fEPSP) were evoked by stimulating Schaffer-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
4
25
1
Order By: Relevance
“…Thus, it is tempting to speculate that CRH co-expression may be associated with different firing patterns of these PV-containing interneuron classes, either through different expression profile of specific voltage-gated ion channels (e.g., K + channels) or via the peptide modulating intrinsic neuronal excitability in an autocrine manner. In pyramidal cells, CRH activation of CRHR1 results in an increase in neuronal excitability at least in part through the inhibition of Ca 2+ -dependent K + channel function (Aldenhoff et al 1983;, as well as through the attenuation of fast A-type and delayed rectifier K-type K + currents (Kratzer et al 2013). Given that such an increase in the excitability of CRH interneurons is not apparent here, and to date, CRH receptors have only been identified on pyramidal cells, it would seem more likely that CRH coexpression may be associated with changes in the expression of ion channels that underlie intrinsic neuronal properties.…”
Section: What Class Of Interneurons Do Crh-expressing Cells Represent?mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is tempting to speculate that CRH co-expression may be associated with different firing patterns of these PV-containing interneuron classes, either through different expression profile of specific voltage-gated ion channels (e.g., K + channels) or via the peptide modulating intrinsic neuronal excitability in an autocrine manner. In pyramidal cells, CRH activation of CRHR1 results in an increase in neuronal excitability at least in part through the inhibition of Ca 2+ -dependent K + channel function (Aldenhoff et al 1983;, as well as through the attenuation of fast A-type and delayed rectifier K-type K + currents (Kratzer et al 2013). Given that such an increase in the excitability of CRH interneurons is not apparent here, and to date, CRH receptors have only been identified on pyramidal cells, it would seem more likely that CRH coexpression may be associated with changes in the expression of ion channels that underlie intrinsic neuronal properties.…”
Section: What Class Of Interneurons Do Crh-expressing Cells Represent?mentioning
confidence: 99%
“…The principal receptor for this peptide, CRH receptor 1 (CRHR1), resides at specific subcellular locations on pyramidal cells (Chen et al 2000), while CRH receptor 2 (CRHR2) is restricted to the axon initial segment of these neurons (Joels and Baram 2009). Electrophysiological studies have demonstrated that within the hippocampus both exogenous and endogenously released CRH, primarily increases pyramidal cell excitability via multiple mechanisms including the inhibition of Ca 2+ -dependent K + channel function (Aldenhoff et al 1983;Haug and Storm 2000; and attenuating A-type K + channel activation (Kratzer et al 2013). CRH is rapidly released within the hippocampus following stress and this peptide has been implicated in mediating some of the stress-induced effects upon hippocampal function (Chen et al 2004(Chen et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Application of CRH results in a rapid dose-dependent increase in the excitability of CA1 and CA3 pyramidal cells [5052], most likely through a reduction in the I AHP that occurs following action potentials [50, 53] and, at least in CA1, the inhibition of A-type K + channel function [54]. Consistent with these effects of exogenous peptide, endogenous CRH increased action potential firing and excitatory transmission onto CA3 pyramidal cells in the acute hippocampal slice.…”
Section: The Temporal Aspects Of the Functions Of Stress-mediators Inmentioning
confidence: 99%
“…Such changes may be mediated by the HPA axis or through the immune system. Treatment of mouse hippocampal slices with corticotropin-releasing hormone seems to alter neuronal excitability depending on L- and T-type calcium channels and also on voltage-gated potassium channels [147]. Antidepressants can alter neuronal excitability by altering calcium and potassium channels, acting as an environmental trigger for mood episodes [148,149].…”
Section: The Phenome Of Bd From the Ion Channel Perspectivementioning
confidence: 99%